Manajemen Model Tata Kelola Berbasis Environmental, Social and Governance (ESG) dalam Penguatan Ekosistem Ekonomi Industri Halal - Wahyuddin, Wawan; Itang, Itang; Peristiwo, Hadi (CV. Lentera Literasi Indonesia, 2025)
The application of Environmental, Social, and Governance (ESG) management principles plays a crucial role in enhancing the competitiveness and sustainability of the halal industry’s economy. The environmental principle emphasizes the need for environmentally friendly halal production through proper waste management, energy efficiency, and the implementation of a circular economy that focuses on environmental preservation. The social principle includes aspects of justice, protection of workers’ rights, community empowerment, and the fulfillment of the halalan thayyiban principles that ensure safety, health, and benefits for consumers. Meanwhile, the governance principle serves to establish a transparent and accountable regulatory system based on sharia values, thereby strengthening public trust and the integrity of the halal industry. This ESG-based governance model not only reinforces the halal industry ecosystem at the national level but also supports the achievement of the Sustainable Development Goals (SDGs) globally. Furthermore, the implementation of this model encourages the halal industry to adapt to international market demands, expand global networks, and increase investment attractiveness based on sustainability. However, challenges in implementation still include regulatory harmonization, consistency in standard application, and the readiness of business actors to fully adopt ESG principles. Therefore, synergy among the government, business sector, academia, society, and halal certification institutions becomes the key to success. This study is expected to provide both conceptual and practical contributions in developing an inclusive, sustainable, and ethically oriented halal industry governance model grounded in sharia values.